Sexuality and postmodernity - Arboccó de los Heros, Manuel (2017)
The following essay contains a group of short texts that are forming a body of reflections on the always complex issue of human sexuality, relationships, and the human being of this post modern society. We can not disconnect the man of his time, so we must place it when something as proper as sexuality we speak. We hope that this work to be of interest and as always we propose, increase the discussion and the debate academic.